The Anti-Tumor Efficacy of Verbascoside on Ovarian Cancer via Facilitating CCN1-AKT/NF-κB Pathway-Mediated M1 Macrophage Polarization - Ren, Yu; He, Jinying; Zhao, Wenhua; Ma, Yuzhen (Frontiers in Oncology, 2022)
Background Ovarian cancer (OC) is the leading cause of gynecological cancer-related mortality. Verbascoside (VB) is a phenylpropanoid glycoside from Chinese herbs, with anti-tumour activities. This study aimed to investigate the effects and mechanism of VB on OC. Methods OC cell lines SKOV3 and A2780 were used in this study. Cell viability, proliferation, and migration were measured using CCK-8, clonogenic, and transwell assays, respectively. Apoptosis and M1/M2 macrophages were detected using flow cytometry. The interaction between VB and CCN1 was predicted by molecular docking. The mRNA expression of CCN1 was detected by RT-qPCR. The protein levels of CCN1, AKT, p-AKT, p65, and p-p65 were determined by western blotting. A xenograft mice model was established for in vivo validation. Results VB inhibited OC cell proliferation and migration in a dose-dependent manner, and promoted apoptosis and M1 macrophage polarization. VB downregulated CCN1 and inhibited the AKT/NF-κB pathway. LY294002, an AKT inhibitor, potentiated the anti-tumour effects of VB. CCN1 overexpression weakened the anti-tumour effects of VB and VB + LY294002. In vivo experiments verified that VB inhibited tumour growth and promoted M1 polarization, which is regulated by the CCN1-mediated AKT/NF-κB pathway. Conclusion VB triggers the CCN1-AKT/NF-κB pathway-mediated M1 macrophage polarization for protecting against OC.